Assessment of antimicrobial prescribing patterns, guidelines compliance, and appropriateness of antimicrobial prescribing in surgical-practice units: point prevalence survey in Malaysian teaching hospitals - Jamaluddin, Nurul Adilla Hayat; Periyasamy, Petrick; Lau, Chee Lan; Ponnampalavanar, Sasheela; Lai, Pauline Siew Mei; Loong, Ly Sia; Tg Abu Bakar Sidik, Tg Mohd Ikhwan; Ramli, Ramliza; Tan, Toh Leong; Kori, Najma; Yin, Mei Kuen; Azman, Nur Jannah; et al. (Frontiers in Pharmacology, 2024)
Objectives: This study sought to investigate the quality of antimicrobial prescribing among adult surgical inpatients besides exploring the determinants of non-compliance and inappropriate prescribing to inform stewardship activities. Methods: A cross-sectional point prevalence study employing Hospital National Antimicrobial Prescribing Survey (Hospital NAPS) was conducted in April 2019 at two teaching hospitals in Malaysia. Results: Among 566 surgical inpatients, 44.2% were receiving at least one antimicrobial, for a total of 339 prescriptions. Antimicrobials belonging to the World Health Organization’s Watch group were observed in 57.8% of cases. Both hospitals exhibited similar types of antimicrobial treatments prescribed and administration routes. A significant difference in antimicrobial choice was observed between hospitals (p < 0.001). Hospital with electronic prescribing demonstrated better documentation practice (p < 0.001). Guidelines compliance, 32.8% (p = 0.952) and appropriateness, 55.2% (p = 0.561) did not significantly differ. The major contributors of inappropriateness were incorrect duration, (15%) and unnecessary broad-spectrum coverage, (15.6%). Non-compliance and inappropriate prescribing were found to be 2 to 4 times significantly higher with antimicrobial prophylaxis prescription compared to empirical therapy. Conclusion: Antimicrobial stewardship efforts to improve appropriate surgical prescribing are essential. These initiatives should prioritize surgical prophylaxis prescribing, focusing on reducing unnecessarily prolonged use and broad-spectrum antimicrobials, raising awareness among prescribers and promoting proper documentation.